Association of Spheranthus africanus (Asteraceae) with other Weeds In a Fallowed Rice Field - Priyadi, Arief; Wibawa, I Putu Agus Hendra; Lugrayasa, I Nyoman (Proceeding International Conference on Global Resource Conservation, 2013)
Spheranthus africanus is a minor weed of rice, which can be utilized for various purposes. It can be used for phytoremediation of soil contaminated with Pb and also reported to have anti-bacterial activity to be used as natural pesticides. However, because of its minority status little is known about this species in its natural habitat. This study was aimed to understanding the relationship between S. africanus with other weed species in a fallowed paddy field in Tabanan District, Bali, Indonesia. Vegetation analysis by quarter method was done in the rice field, where the species had occurred, in 2011 and 2012. Determination of association type between S. africanus with other weed was conducted by using 2x2 contingency table to calculate Ï2, association coefficient (AC) and Ochiai index (OI). The result shows that the Shannon diversity index in this same area for the two consecutive years were 2.06 and 2.48 with species richness of 22 and 27 respectively. Calculation of Summed Dominance Ratio (SDR) showed that the species composition was not evenly distributed, in other words some species dominated others. In terms of association, although S. africanus mainly has no association with most of the weed species in the field, it prominently has positive association with Lindernia ciliata, and Digitaria ciliaris, with no significant negative association. Keywords: diversity, species association, Spheranthus africanus